First record of the genus Brachyzapus Gauld & Dubois, 2006 (Hymenoptera: Ichneumonidae: Pimplinae) from the Afrotropical region, with descriptions of two new species - Varga, Oleksandr; Reshchikov, Alexey; Giovanni, Filippo Di (Zootaxa, 2018)
Brachyzapus Gauld & Dubois, 2006 is a small genus belonging to the Polysphincta genus-group of the subfamily Pimplinae, with nine known species worldwide (Uchida & Momoi, 1958; Yu et al., 2012; Pham et al., 2012). The genus can be recognized by twisted mandibles, a very weakly convex and rather long clypeus with quite well-defined angulation laterally, elongate lower face, sparse pubescence on the eyes, hind coxal cavities separated from the metasoma insertion by a very strong sclerotized bridge, and the lack of a basal lobe on the ovipositor (Gauld & Dubois, 2006).